198k views
0 votes
-3(n+3) - 10(8n + 9)

User Austine
by
5.0k points

2 Answers

2 votes

Answer:

= − 77n − 81

I hope this helps you and you get it right this is if you simplify it I don’t know what you are really looking for sorry if it is wrong. :)

User Kurdtc
by
5.6k points
4 votes

−3(n+3)−10(8n+9)

(−3)(n)+(−3)(3)+(−10)(8n)+(−10)(9)

=−3n+−9+−80n+−90

=−3n+−9+−80n+−90

=(−3n+−80n)+(−9+−90)

=−83n+−99 <- ANSWER

User Callam
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.